1976
DOI: 10.1093/geronj/31.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Remarriage Probability After Widowhood: A Retrospective Method

Abstract: A technique was devised to estimate age specific remarriage probabilities for newly widowed persons utilizing North Carolina marriage certificates plus informatiom from the 1970 U. S. Census. Remarriage probabilities are very high for persons widowed before age 35. Remarriage probabilities decrease faster for widows than widowers. Less than one-fourth of men widowed after age 65 ever remarry. Less than 5% of women widowed after age 55 ever remarry. Age specific intervals to remarriage were also calculated. Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Increasing life expectancy and a transformed age structure from the young to the old are changing every aspect of our lives (Wise, 1989). An aging population and longer individual life-spans raise important concerns about the impact of late-life events upon the well-being of the elderly (Cleveland & Gianturco, 1976;Wise, 1989). One of the most significant late-life events for elderly couples is the death of a spouse.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing life expectancy and a transformed age structure from the young to the old are changing every aspect of our lives (Wise, 1989). An aging population and longer individual life-spans raise important concerns about the impact of late-life events upon the well-being of the elderly (Cleveland & Gianturco, 1976;Wise, 1989). One of the most significant late-life events for elderly couples is the death of a spouse.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, both married and unmarried men were more likely to spend a higher proportion of their future life years married as compared to married and unmarried women, respectively. This would mean that a married woman would be far more likely to become a widow, as opposed to a married man becoming a widower and, not surprisingly, investigators have found that older men are more likely to remarry as compared to older women ( Cleveland & Gianturco, 1976 ; Federal Interagency Forum on Aging-Related Statistics, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…particularly among women (Cleveland & Gianturco, 1976;Treas & Van Hilst, 1976). In one piece of research, Wilson and DeShane (1980) found that divorced individuals in a sample of per sons over age 65 had occupied that marital status for an average of 19.2 years.…”
Section: Divorce Rates Among the Elderlymentioning
confidence: 99%